Adequacy of Preoperative Counseling and Informed Consent at Shree Birendra Hospital - Sharma, Sharaswati; Joshi, Amit (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Preoperative counseling is the physical and psychological preparation of a patient prior to surgery. In recent past, a surge of unrest seen in our country was mostly because of inadequate counseling. There are very limited researches conducted to analyze the adequacy of counseling in surgical patients. The aim of this study was to analyze the adequacy of counseling in patients admitted for surgical procedure at division of surgery, Shree Birendra Hospital. Methods: A prospective survey was done using set questionnaire to the patients who are admitted for surgery over a period of 2 months (May- July 2012). All Patients who were admitted to Gynaecology, General Surgery, Orthopedic and ear nose and throat (ENT) department for a major elective surgical procedure, were included in this study. Those who have already undergone some surgery in the past or patients admitted for emergency surgery were excluded. Results: Among 100 consecutive patients, 44 patients were graded as inadequately counseled. There were 28 patients who were categorized as illiterate; the counselling was inadequate in17 (60.7%). Among 100 cases, 50 were counseled by the treating doctors, and only 10 (20%) counseling by them were inadequate. Whereas the inadequacy of counseling was 57.69% and 79.16% respectively in those who were counseled by nurses or the family members. Conclusions: Counseling was inadequate in 44% of patients. Inadequacy of counseling was higher in illiterate and if counseling is done by anybody other than treating physician. Medical Journal of Shree Birendra Hospital; January-June 2013/vol.12/Issue1/11-13 DOI: http://dx.doi.org/10.3126/mjsbh.v12i1.9085